Posttraumatic stress disorder among patients with oral and maxillofacial trauma in a South Indian population. (7th May 2019) - Nayak, Sunil S.; Kamath, Abhay T.; Gupta, Kripa; Roy, Anubhav; Roy, Sreea; Chatterjee, Abhirup
Abstract: Aim: To determine the incidence and severity of Post‐Traumatic Stress Disorder (PTSD) in maxillofacial trauma patients and to assess the predisposing factors. Methods and Results: Post‐Traumatic Stress Disorder (PTSD) was assessed as per the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM‐5) criteria. The PTSD checklist for DSM‐5 (PCL‐5), was used initially to screen patients for PTSD for a provisional diagnosis. These provisionally diagnosed patients were then subjected to a structured interview by a Clinician Administered PTSD Scale for DSM‐5 (CAPS‐5). The PTSD status outcome of PCL‐5 and CAPS‐5 were correlated. PTSD was compared among patients with different types of facial fractures/injuries and also compared based on their anatomic location. The reliability of PCL‐5 scale in relation to the structured CAPS‐5 was assessed and the specificity was found to be 71.4%. Patients with both aesthetic and functional deformity exhibited greater severity of injury and showed higher incidence of PTSD with higher conversion rate from the 1st month to 3rd month. The frequency of PTSD in deformities with higher severity like zygomaticomaxillary complex injuries was found to be statistically significant. Conclusion: A high incidence of PTSD is associated with maxillofacial trauma and early detection is essential.